Peningkatan Hasil Belajar Ilmu Pengetahuan Alam Tentang Energi Bunyi Melalui Metode Demonstrasi Pada Peserta Didik Kelas IV Semester Genap Sekolah Dasar Negeri 02 Belikurip - Endar Januanto (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The purpose of this research was to improve student learning outcomes in the science subject of sound energy in grade IV elementary schools through the demonstration method. The research conducted was a Classroom Action Research (PTK) consisting of 4 stages, namely planning, implementation, observation and reflection. Each meeting there is an increase in learning outcomes as evidenced by the increase in student completeness in each cycle. In the pre-cycle stage, completion was only 33.33% (4 students completed and 8 students did not complete), while for cycle I it reached 66.67% (8 students completed and 4 students did not), for cycle II the increase in completion reached 83.33% (10 students completed and 2 students did not complete). These data show that the indicators of success have been achieved, namely more than 75% of students got a score ≥ KKM 65. These results show that the application of thedemonstration method can improve science learning outcomes in sound energy material for class IV students at SDN 02 Belikurip.